(untitled) (Bangladesh Journal of Medicine, 2015)
Tuberculosis is one of the most common diseases in Bangladesh and has variable clinical manifestations. Isolated Hepatic tuberculosis is not a common disease; in fact the presentation of hepatic tuberculosis may be without having history of any active Pulmonary TB or military TB. Patient usually present without having any typical symptoms; so it is difficult for a physician to diagnose the disease quickly. Patient presenting with space occupying lesion in liver is confused with abscess, hepatoma or metastases. Here we are presenting a case report of isolated hepatic tuberculosis. Bangladesh J Medicine Jan 2015; 26 (1) : 43-45